Produtividade de cafeeiros em sistema agroflorestal - Nannetti, Alex Nogueira (2012)
The purpose of this study was to analyze the development and the production of the coffee tree Red Icatu, lineage 2945, under agroforestry system in different conditions of shade: next to the stalk of the trees (shadowed), inside of the crown of the tree (half shadowed), and out of the crown of the tree (in the sun). The experimental area lies on the mountain region in the south of Minas Gerais, in the municipality of Machado, where there is a prevalence of Jacarandá Paulista trees (Macherium villosum Vog., familia Leguminosae Papilionoideae), which provided the different shading conditions for the coffee trees. The data were collected from the three shading conditions between July and September 2011, on two coffee plants, with seven replications for each treatment. Productivity data were analyzed, as well as stalk diameter and height of the coffee trees. They were submited to the statistic analyzis by the SISVAR Program, by the Scott-Knott Test to 1%. There was a better development of the plants (stalk diameter and height of the plant) as well as a larger productivity of grains for the coffee trees which lay in half shadow.